QUALITY INCENTIVES FOR SELECTED FOOD PRODUCTS - Harianto Harianto (Departemen Agribisnis, FEM-IPB, 2009)
The increasing income has demanded more various and better quality of agricultural products in the market. The society with better living standard also demanded a more comfortable shopping environment. This paper aims to investigate if the food price is influenced by the product characteristics and shopping environment. The hedonic price function model was used to analyze the influence of product characteristics and shopping ennvirontment to the price. As the sample case, rice, mungbean and peanuts have been selected. The data were collected from the retailers in Jakarta. The result showed that the product characteristics and shopping environment influenced the prices of rice, mungbean and peanuts. The implication of this study is the consumers are willing to pay higher price in order to get better quality and more comfortable shopping environment.